Search
Ask a question
0 0

simplify and solve

 
simplify
 
1.  (3x)^1/3     I have 3x^2/3
                                    3x
 
 
2.  -x^2y^2
      x^1/2 y^0
Tutors, please sign in to answer this question.

2 Answers

(3x)1/3 cannot be further simplified
 
-x2y2/x1/2y0 = (-x2x-1/2)y2/1 (-x2-1/2)y2 = -x3/2y2
 
 
Your answer is not right,
 
(3X) X ^( 2/3 ) / 3X = 1/ ( 3x ) ^-1/3  this is not any simplification, only use of negative exponent.
 
only way is to write in the radical form
 
 
  (3X ) ^ 1/3 = 3√3X 
 
 
2. - x ^2 Y^2   = - X ^( 3/2) . Y ^2
    X ^1/2 Y 0
 
   
 

Comments